2019
DOI: 10.3892/etm.2019.8112
|View full text |Cite
|
Sign up to set email alerts
|

Increased temperature‑related adeno‑associated virus vectors transduction of ovarian cancer cells ‑ essential signatures of AAV receptor and heat shock proteins

Abstract: Recombinant adeno-associated viruses (rAAVs) are becoming more commonly used in clinical trials involving gene therapy. Additionally AAV-based drugs have already been registered. Gene therapy aims to increase transduction efficiency, increase in vivo selectivity and reduce side effects. One approach to achieve this is the use of physical factors, such as temperature or more specifically, hyperthermia, which is already utilized in oncology. The aim of the present study was to investigate the effect of hyperther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(83 reference statements)
1
1
0
Order By: Relevance
“…They were all overexpressed and signi cantly correlated with poor survival in OCs. Previous studies have found that EZR [18], HSPG2 [19] and SLC9A1 [20] were potential targets for the treatment of OC, which are consistent with our analysis results. Subsequently, patients with elevated SLC9A1 expression had an advanced histologic grade, however, the EZR and HSPG2 expression levels were not notably associated with the clinicopathological factors.…”
Section: Discussionsupporting
confidence: 93%
“…They were all overexpressed and signi cantly correlated with poor survival in OCs. Previous studies have found that EZR [18], HSPG2 [19] and SLC9A1 [20] were potential targets for the treatment of OC, which are consistent with our analysis results. Subsequently, patients with elevated SLC9A1 expression had an advanced histologic grade, however, the EZR and HSPG2 expression levels were not notably associated with the clinicopathological factors.…”
Section: Discussionsupporting
confidence: 93%
“…The AAV could infect nondividing cells and integrate its genes engineered by researchers into the specific site of human genes to express proteins for killing cancer cells. So far, the AAV has been employed to treat many types of cancers, 162 such as liver cancer, 163 colorectal cancer, 164 lung cancer, 165 glioblastoma, 166–168 breast cancer, 169 leukemia, 170 mesothelioma, 171 pancreatic cancer mice, 172 cervical cancer, 173 ovarian cancer, 174 melanoma cells,, 175 and bone cancer 176 …”
Section: Virus Nanoparticlesmentioning
confidence: 99%